Thoughts on Islamic Education According to Abbas Pulungan - Triyanda Pohan, Sonya Elsa; OK, Azizah Hanum; Usiono, Usiono (Edumaspul: Jurnal Pendidikan, 2024)
Education is the most important means of developing children’s potential. The development of children’s potential will be achieved optimally, if education can be carried out well. Humans really need education to develop their potential, so that it is useful for civilization. This research aims to examine literature reviews related to Abbas Pulungan’s thoughts on Islamic education. The research method uses the SLR (Systematic Literature Review) method. Data collection was obtained by documenting articles related to similar research. The articles that can be used in this research are 5 national journal articles that can be obtained from the Google Scholar database using the publish or perish application. Based on research, it can be seen that good character education can be instilled from an early age and good educational institutions related to cultivating children’s character are located in Islamic boarding schools